2005
DOI: 10.1007/s00467-005-2006-6
|View full text |Cite
|
Sign up to set email alerts
|

Chloroacetaldehyde- and acrolein-induced death of human proximal tubule cells

Abstract: Ifosfamide (ifo) is a commonly used drug in chemotherapy. It is metabolized to acrolein (acro) and chloroacetaldehyde (CAA), which are thought to be responsible for renal side effects. We studied the effects of ifo and cyclophosphamide (cyclo) as well as their metabolites, acro and CAA, on cellular protein content, necrosis, apoptosis and cytosolic calcium concentration using a human proximal tubule cell line. The protein content decreased during acro or CAA administration (15 to 300 micromol/l), but not durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…6A). This mode of action may explain previous observations indicating that CAA depleted cellular reduced glutathione and ATP, disturbed Ca 2+ signaling, lipid peroxidation, and, ultimately, cell necrosis and death (8,(35)(36)(37)(38)(39). The cytotoxic effect of CAA is likely due to low or no reactivity with MESNA (Fig.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…6A). This mode of action may explain previous observations indicating that CAA depleted cellular reduced glutathione and ATP, disturbed Ca 2+ signaling, lipid peroxidation, and, ultimately, cell necrosis and death (8,(35)(36)(37)(38)(39). The cytotoxic effect of CAA is likely due to low or no reactivity with MESNA (Fig.…”
Section: Discussionsupporting
confidence: 63%
“…In addition to the curtailment of ATP synthesis, dysfunction of C-I may lead to elevated production of superoxide radicals, causing mitochondrial DNA mutations, lipid peroxidation, and protein denaturation (35)(36)(37)(38). The current study shows that the IFOinduced inhibition of NADH:oxidoreductase was associated with a significant elevation of [NADH], inhibition of the flux through the PDH reaction, and incorporation of acetyl-CoA (derived from pyruvate) into the TCA cycle (Figs.…”
Section: Discussionmentioning
confidence: 58%
“…6, 7). These concentrations are well below the 150 μM acrolein needed for initiation of toxicity in human proximal tubule cells (Schwerdt et al, 2006). Furthermore, the tubule cells were serum-deprived for 24 hr before acrolein treatment (Schwerdt et al, 2006) whereas the HMEC-1 cells in our studies were not.…”
Section: Acrolein-mediatedmentioning
confidence: 78%
“…56,57 It has been reported that necrosis is the predominant form of cell death by chloroacetaldehyde in human proximal tubular cell lines. 58 Furthermore, chloroacetaldehyde caused elevations of intracellular free Ca2+ by an inhibitory action on Na+/ Ca2+ exchanger, which ultimately led to the disruption of membrane integrity. 59 Nitric oxide (NO) has an important role in modulating oxidative stress and tissue damage.…”
Section: 50mentioning
confidence: 99%